Valuasi nilai guna langsung Mata Air Sembat - F A Alfendo; C A Napitupulu; Muhammad Ainun Najib (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
Clean water is very important to ensure the survival of all living things, especially humans. Clean water contributes directly and indirectly to economic and ecology. The purpose of this study was to predict the monetary value of Springs Sembat resources as a provider of raw water in 2021 using the real market price method. The research was conducted on December 9, 2021, in the Springs Sembat area, which is administratively located in Kota Baru District, Jambi City, Jambi Province. The data were analyzed using economic valuation techniques. This valuation examines the direct use value of the use of the Sembat Springs source, namely the market value of the quantity of water produced minus the cost of water treatment. Based on the results of the study, it was found that the direct use value of the Sembat Springs ecosystem in 2021 was IDR 807,800,000, without considering the aspects of maintaining water treatment equipment, maintenance of distribution pipes, and worker wages.